MON-082 The Neonatal Screen That Cried Wolff - D’Ambrosio, Fabiola (J Endocr Soc, 2020)
Introduction: Hypothyroidism is one of the major causes of preventable mental retardation. Neonatal screening aids in the prompt diagnosis of newborns with congenital hypothyroidism. There are other clinical conditions that can alter thyroid function during the newborn period, including exposure of high iodine concentrations. Case Presentation: One day old female born at 37 3/7 weeks of gestational age by C-section with imperforated anus and congenital heart disease was transferred to our children’s hospital within the first day of life for a hybrid cardiac procedure of bilateral pulmonary artery banding and PDA stenting. She had an Illinois Neonatal screen done at 36 hours of life that was normal. Her cardiac surgery was performed at 10 days of life, where she was exposed to iodine products transdermally. At 14 days of age, she had a repeat Illinois Neonatal screen that was positive for congenital hypothyroidism with a TSH of 78 mIu/mL (normal < 20 mIu/mL) and reflex total T4 of 5.4ug/dL (normal is > 8ug/dL). No family history of thyroid disease; mother was healthy during pregnancy and was not on medications that could affect baby’s thyroid function. Subsequent serum laboratory testing confirmed a TSH of 74.3mIu/mL and Free T4 of 0.6ng/dL. Patient was diagnosed with Wolff-Chaikoff effect, which is the phenomenon of transient hypothyroidism caused by exposure to high doses of iodine (iodine containing contrast agents or topical antiseptics). Pediatric Endocrinology was consulted at 2 weeks of life and she was started on 25mcg of levothyroxine PO daily. Levothyroxine dose decreased at 16 month of age to 12.5mcg due to stable thyroid function tests. The patient was last seen at 30 months of age by Pediatric Endocrinology. She is still on the low dose of levothyroxine and her thyroid labs have been within normal limits for an infant. She will likely not require lifelong thyroid supplementation. Conclusion: Risk of hypothyroidism among neonates must be considered seriously after large iodine exposure and monitoring for transient hypothyroidism should be performed. It is thus recommended that attempts should be made to reduce the amount of iodine used during procedures and to carefully monitor thyroid function in all neonates exposed to an excess of iodine. Reference: Markou, K., et al. “Iodine-Induced Hypothyroidism.” Thyroid, vol. 11, no. 5, 2001, pp. 501–510., doi:10.1089/105072501300176462. Linder N, Sela B, German B, et al. Iodine and hypothyroidism in neonates with congenital heart disease. Archives of Disease in Childhood - Fetal and Neonatal Edition 1997;77:F239-F240. Kovacikova, Lubica, et al. “Thyroid Function and Ioduria in Infants after Cardiac Surgery: Comparison of Patients with Primary and Delayed Sternal Closure.” Pediatric Critical Care Medicine, vol. 6, no. 2, 1 Mar. 2005, pp. 154–159., doi:10.1097/01.pcc.0000154960.59452.06.